Prediction of elastic behaviour and initial failure of textile composites - Crookston, Jonathan Josiah (2004)
When a component is produced from textile reinforcement, it is well known that the reinforcement conforms to the shape of the tooling, predominantly by in-plane shear deformation. Current structural analysis techniques for composite components frequently neglect the effects of this deformation on subsequent mechanical properties. In this thesis the effects of shear deformation in the reinforcement on mechanical properties of the composite are shown to be significant, both for flat laminates with uniform reinforcement deformation, and for a component where deformation changes over the geometry.